Effects of Yogic Practices and Physical Exercises on Breath Holding Time among Type II Diabetes Patients: Effects of Yogic Practices and Physical Exercises on Breath Holding Time among Type II Diabetes Patients (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study was done to find out the effect of yogic practices and physical exercises on breath holding time among type II diabetes patients. To achieve this purpose, thirty Type II women diabetic patients (n = 30) from Rajah Muthiah Medical College, Annamalai University were randomly selected as subjects. The age of the subjects ranged from 35 to 40 years. The subjects divided into three equal groups of ten subjects each (n = 10). In which, group I underwent yogic practices (YG), group II underwent physical exercises (PG) for six days per week for twelve weeks and group III acted as control (CG) who did not undergo any special training programme apart from their regular activities. The selected criterion variable such as breath holding time was assessed by using holding the breath for maximum duration before and after the training period. The data collected was analysed by administering the Analysis of Covariance (ANCOVA). Scheffe’s test was also administered as post hoc test to determine if there existed any paired mean difference. From the results of the study, it was found that there was a significant increase (p ≤ 0.05) in breath holding time of training groups when compared to control group.